2020
DOI: 10.4103/jfmpc.jfmpc_1098_20
|View full text |Cite
|
Sign up to set email alerts
|

The age–friendly cities characteristics from the viewpoint of elderly

Abstract: Background: Elderly population is rising due to advancement of health care, medical services, and increasing life expectancy. World Health Organization (WHO) has initiated a global project to define “age-friendly city for improving the elderly's quality of life”. Objectives: The purpose of the study was to determine the age-friendly cities characteristics from the elderly's point of view in Gorgan, Iran. Methods: This cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Main threats to age-friendly systems identified at the person level were differences in individual perceptions and acceptance of roles and importance 48,54,86 of champions (e.g., advocates) and partnerships 77 and need to educate service providers to support older adults. 57 Main threats to age-friendly systems identified at the system level were readiness for change, 48,51 adapting to needs of older adults, 36,56,85,89 community 44,63,68,77,78,82 and health system 31,62,66,81 barriers, challenges in poor/developing areas, 84,88 and additional COVID-19 related barriers. 28…”
Section: Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main threats to age-friendly systems identified at the person level were differences in individual perceptions and acceptance of roles and importance 48,54,86 of champions (e.g., advocates) and partnerships 77 and need to educate service providers to support older adults. 57 Main threats to age-friendly systems identified at the system level were readiness for change, 48,51 adapting to needs of older adults, 36,56,85,89 community 44,63,68,77,78,82 and health system 31,62,66,81 barriers, challenges in poor/developing areas, 84,88 and additional COVID-19 related barriers. 28…”
Section: Threatsmentioning
confidence: 99%
“…(2) interpersonal connectedness, 42 community, 63,70 and participation 52,89 in age-friendly systems; (3) organizational integration and planning, 39,42,48,51,91,93 characteristics, 47,48 collaboration, 82 funding 41,77,78 ; and (4) environmental fit, 36,40,70 transportation and access, 61,85,87,89,92 jurisdiction, 63 and built environment. 34,37,44,56,89…”
Section: Structural Factorsmentioning
confidence: 99%
“…These results are inconsistent with other studies in areas with similar economic conditions but different climates. A study on age-friendly cities in a cold semi-arid climate zone concluded that the most significant factor in public transportation was seats for the elderly and special facilities for the disabled, and the amount of public transportation was not discussed [68]. Another study on the travel behaviour of the elderly in a tropical rainforest climate zone showed that the majority of the elderly (62.46%) travelled by private transportation, followed by public transportation (20.47%) [69].…”
Section: Marginal Effectsmentioning
confidence: 99%
“…[ 2 ] Nowadays, due to the increasing life expectancy and decreasing fertility in the world, aging has turned into a global phenomenon. [ 3 ] Based on the World Health Organization, the elderly population will touch 2 billion by 2050. Therefore, the elderly population has the fastest population growth rate among different age groups and approximately, two-thirds of all the elderly people live in developing countries.…”
Section: Introductionmentioning
confidence: 99%